PROTECTION AND SUSTAINABLE DEVELOPMENT ECOSYSTEM DANUBE REGION - Mijajlovic, Nada; Cvijanović, Drago; Stajkovac, Jugoslav (Economics of Agriculture, 2011)
The natural ecosystems of the Danube region along the entire course of the Danube are exposed to serious pollution originating from human mining-energy activities . Given the mineral resources that are established in the countries through which the water of the Danube and the activities carried out by a man in order to exploit signifcantly disrupt ekosisitemi. The aim of this paper is to highlight the rich biodiversity of the Danube region with special emphasis on the Djerdap National Park, as well as vulnerability and exposure to pollution by several factors and the necessity of taking measures to protect these ecosystems. Many documents have been adopted on measures to be taken to protect the Djerdap as a national good.